Structural Analysis via Cellular Automata: Parameters of Wings of Boeing 737 - Mohamed Suffian, Mohd. Harridon (2006)
The role of cellular automata is comprehensively within the genre of structural analysis as the compendium of areas is subdivided into sectional areas which are called cells. A cell contains characteristics or traits of the area being analyze where this area is bounded or contained in the cell. Individual cell is represented by differential equations that would govern the endeavours of the designated cell. The alteration of attributes of an individual cell would affect the traits of the neighbouring cells. This is the primary gist of cellular automata, the dependable entities of surrounding parameters. This paper delineates the advent of the usage of cellular automata in the procreation of analysis of a structure. The chosen structures are the wings (right and left) of Boeing 737. The wings are partitioned into cells and the methodologies of cellular automata as bestowed earlier are parlayed. Results of the analysis are compared with conventional data of the same genre (Boeing 737) which postulates and stipulates the deterministic nature of cellular automata. The variables (individual cells) that are dependable are measured in accordance with the rate of alteration of cells and the domino affect of it. These are tabulated and would give a comprehensive structural analysis.